1997
DOI: 10.1046/j.1365-2036.1997.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin, amoxycillin and H2‐receptor antagonist therapy for Helicobacter pylori peptic ulcer disease in Korea

Abstract: Background: Effective anti‐Helicobacter pylori therapies with few side‐effects are needed. We previously showed that the regimen of amoxycillin, clarithromycin and an H2‐receptor antagonist was effective in the United States. The current study tested whether this therapy would also be successful in Korea. Methods: Patients with gastric or duodenal ulcers received amoxycillin (750 mg t.d.s.) plus clarithromycin (500 mg t.d.s.) for 2 weeks and nizatidine 300 mg at bedtime for 6 weeks. Endoscopic examinations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
2
12
0
Order By: Relevance
“…The low power of this study, however, does not allow us to conclude that ranitidine‐ and omeprazole‐based regimens can be considered equivalent. However, our findings achieved in a trial comparing head‐to‐head proton pump inhibitor‐ and H 2 ‐RA‐based triple therapies reinforces the results reported in previous studies assessing the efficacy of these drug combinations separately or together in small sample trials, 13 –21 and leads us to question the importance of profound acid suppression in the eradication of the bacterium.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The low power of this study, however, does not allow us to conclude that ranitidine‐ and omeprazole‐based regimens can be considered equivalent. However, our findings achieved in a trial comparing head‐to‐head proton pump inhibitor‐ and H 2 ‐RA‐based triple therapies reinforces the results reported in previous studies assessing the efficacy of these drug combinations separately or together in small sample trials, 13 –21 and leads us to question the importance of profound acid suppression in the eradication of the bacterium.…”
Section: Discussionsupporting
confidence: 87%
“…More importantly, doubling the dosage of clarithromycin from 500 to 1000 mg/day decreased the success of the treatment. Furthermore, although clarithromycin is known to be a powerful antibiotic against H. pylori , it has been suggested that clarithromycin resistance may reduce the efficacy of triple regimens combining this drug with an H 2 ‐RA and amoxycillin 20 . This makes it easy to predict a lower than expected success in populations with a high prevalence of background clarithromycin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Multiple studies and trials have been published that include the H 2 receptor antagonists as anti-secretory agents, with relatively encouraging results. [4][5][6][7][8][9][10][11][12] The first thing to do is thus to consider whether the PPIs are superior to the anti-H 2 in this indication. On the one hand the PPIs possess, different to the H 2 receptor antagonists, intrinsic antibacterial activity against H. pylori, [13] besides producing a synergic pharmacokinetic interaction with the antibiotics.…”
Section: Ppis Versus Histamine H 2 Receptor Antagonistsmentioning
confidence: 99%
“…The benefit of PPIs in eradication therapy is mainly due to acid suppression as described above, and H2RAs can be substituted for PPIs and maintain high eradication rates [38,39]. For example, some randomized controlled studies showed the same eradication rates between PPIbased and H2RA-based 1-week triple therapies [65,66].…”
Section: (1) Ppis and H2ras In Combination Therapiesmentioning
confidence: 98%
“…The effect of PPIs in combination therapies may be a synergistic effect. Because H2RAs have no antibacterial activities in vitro (Table 1) and also produce high eradication rates (89%-95.8%) in combination therapies, it is as likely that the primary effect is suppression of acid rather than the antimicrobial activity [38,39]. Because bismuth has different antibacterial mechanisms from other antibiotics and resistance has not been reported, it has been used in the combination therapy for H. pylori infection [33].…”
Section: (6) Proton Pump Inhibitors (Ppis) and Histamine H2-receptor mentioning
confidence: 98%